Proceedings of the 2019 Federated Conference on Computer Science and Information Systems 2019
DOI: 10.15439/2019f192
|View full text |Cite
|
Sign up to set email alerts
|

Non-dominated Sorting Tournament Genetic Algorithm for Multi-Objective Travelling Salesman Problem

Abstract: A Travelling Salesman Problem (TSP) is an NPhard combinatorial problem that is very important for many real-world applications. In this paper, it is shown, that proposed approach solves multi-objective TSP (mTSP) more effectively than other investigated methods, i.e. Non-dominated Sorting Genetic Algorithm II (NSGA-II). The proposed methods use rank and crowding distance (well-known from NSGA-II), combining those mechanisms in a novel, unique way: competing and coevolving in the evolution process. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In order to solve these problems, the suggested algorithm has high convergence with minimum local value. Myszkowski et al [5] suggested a new method to solve multiobjective TSP (they notation it by mTSP) where this method is better than other methods which is called Sorting Genetic Algorithm II (NSGA-II). The new modification considers the improvment of the results which are verified by the benchmark of (mTSP).…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, the suggested algorithm has high convergence with minimum local value. Myszkowski et al [5] suggested a new method to solve multiobjective TSP (they notation it by mTSP) where this method is better than other methods which is called Sorting Genetic Algorithm II (NSGA-II). The new modification considers the improvment of the results which are verified by the benchmark of (mTSP).…”
Section: Introductionmentioning
confidence: 99%